Pengaruh Size of Firm, DAR, dan Struktur Kepemilikan Manajerial Terhadap Manajemen Laba dengan Penerapan Prudence Sebagai Pemoderasi - Nur Ramawati; Lestari Adhi Widyowati (Jurnal Multidisiplin Madani, 2022)
This study aims to analyze the effect of size, DAR, and managerial ownership structure on earnings management by applying prudence as moderating both simultaneously and partially. The population in this study are manufacturing companies in the automotive industry and its components which are listed on the Indonesia Stock Exchange for the period 2012-2016 with a total population of 12 companies. The method used in this study is a quantitative method with the type of research is causality. Data analysis used the Moderated Regression Analysis (Moderated Regression Analysis) with SPSS 20. Then tested using the classical assumption test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), and hypothesis testing (F Test, T Test). The results of the study simultaneously state that size, DAR and managerial ownership structure have a significant effect on earnings management. Partially stated that the size and structure of managerial ownership have a significant effect on earnings management, while DAR has no significant effect on earnings management. Prudence can simultaneously moderate the effect of size, DAR and managerial ownership structure on earnings management. Partially Prudence can moderate the effect of size on earnings management.